Groundnut Shell Particleboard As an Alternative to Sawdust Particleboard - Aqlan Azman, Muhammad Aqil; Naser, Mohamad Aiman; Mustafa Kamal, Muhammad Asyraaf; Ab Razak, Siti Noraiza (Multidisciplinary Applied Research and Innovation, 2025)
This project focuses on the innovative use of agricultural waste, especially peanut shells, in producing particle board, as well as being a sustainable and environmentally friendly alternative to conventional wood-based products. Particle board from groundnut shell (GS), coconut husk (CH) and rice husk (RH) were produced using casein-based adhesive of ratio 1:1, respectively. A hot and press machine was used at temperature of 150°C and compressed load of 1 tonned. The samples underwent a strength test, density and granular structure analysis. From the strength test, GS particle board was identified to be the strongest board compare to CH and RH as it can bear the maximum load of 400 g. This is due to higher density of GS particle board that is 244.44 kgm-3. The granular structure of GS particleboard shows the most compacted and compressed which is considered as the most perfect structure of particle board. The data collected from these tests reveal varying outcomes in terms of strength across the different particleboard compositions.